Assessment of infection control practice in private dental hospital - Yadav, Bipin Kumar; Rai, Ambesh Kumar; Agarwal, Savita; Yadav, Bindu (International Journal of Research in Medical Sciences, 2017)
Background: The purpose of this study was to assess the awareness and practice of infection control procedures among dental surgeons in the private dental hospital. Methods: This is an observational study conducted among thirty dental surgeons working in a private dental hospital in Gwalior, (M.P.) to evaluate the management policies and procedures associated with infection control and instrument decontamination. The doctors were indirectly interviewed by self-administered questionnaire consisted of twenty-one questions regarding the availability of infection control materials, use of personal protective devices, techniques of hand washing, sterilization methods, control of aerosols, status of immunization, asking about medical history, routine documentation of needle-prick injuries, methods of waste segregation etc. The study group was selected regardless of sex, age and field of expertise. This study was done in two weeks and in this time frame self-administered, pre-structured questionnaire was offered to professionals. Results: In this study it was found that although 95% of doctor’s wear gloves but only 6.6% doctors use protective eyewear and 3.3% use gowns for protection. The most of the doctor’s use soap bars for hand washing which is also not a good infection control practice method. There are only 10% doctors who use high-volume-evacuator but most of the time available evacuator is not in working state. Not a single doctor used rubber dam. Out of thirty 74% use gluteraldehyde, 67% use sodium hypochlorite, 54% use phenolic compounds as a surface disinfectant. Most of the doctors use non-sterilized hand pieces, burs, impression trays etc. Conclusions: The infection control actions implemented by dental surgeons were far from ideal. Efforts are needed to improve attitudes, encourage implementation, raise awareness, promote regular updating courses and motivate dental professionals in the correct and routine use of infection control measures. Apart from this, it is also important to improve the hospital management system.